Factorial study of diesel engine oil contamination effects on steel and ceramic sliding contacts. (May 2019) - Ramkumar, P; Harvey, TJ; Wood, RJK; Rose, AD; Woods, DC; Lewis, SM
The present work investigates the effects of diesel contaminants and their interaction on tribological properties for bearing steel (En31) and ceramic (Si3 N4 ) sliding contacts using a factorial study. The contaminants are soot, sulphuric acid, moisture and oxidation, and each contaminant has three different level of concentration (low, medium and high) in the test matrix. The factorial test matrix consisted of 20 tests, constructed from a quarter fractional factorial test matrix with four points at the medium values for the contaminants. Results from this matrix required six further tests to elucidate aliased pairs of interactions using Bayesian model selection. A pin-on-disc tribometer was used to carry out all the experiments. All tests were carried out under ambient conditions at 5 m/s sliding speed and contact stress of 1.5–2.05 GPa to simulate a valve-train in a diesel engine with fully formulated heavy-duty diesel engine oil used as lubricant. Four different tribological properties were studied. The factorial study showed that charge was influenced by tribocouple material; the silicon nitride discs produced higher charge than steel discs. However, it was opposite for friction ; the silicon nitride disc gave lower friction and the pins showed higher friction than their steel counterparts. For wear scar and temperature, soot contaminant was found to be important. The two important interactions were found for the charge response, with the interaction between sulphuric acid and pin material being more important than sulphuric acid–oxidation interaction. Similarly to charge, an interaction between sulphuric acid and pin material interaction was found for friction.